2016
DOI: 10.1590/s0080-623420160000700019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dignity therapy on terminally ill patients: a systematic review

Abstract: OBJECTIVE Analyzing the evidence of the effects of dignity therapy onterminally ill patients. METHOD A Systematic review of the literature conducted using the search strategy in six databases. Inclusion criteria were primary studies, excluding literature reviews (systematic or not) and conceptual articles. RESULTS Ten articles were analyzed regarding method, results and evidence level. Dignity therapy improved the sense of meaning andpurpose, will to live, utility, quality of life, dignity and family appreciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 20 publications
3
41
0
8
Order By: Relevance
“…Life review/dignity therapy Adults and mixed samples Patient outcome: meaning and purpose 3 SRs 100,103,107 In one review of life review interventions, two RCTs found no significant differences in purpose in life between life review and control groups. Owing to reported heterogeneity, pooled estimates were not calculated.…”
Section: (In)mentioning
confidence: 99%
See 4 more Smart Citations
“…Life review/dignity therapy Adults and mixed samples Patient outcome: meaning and purpose 3 SRs 100,103,107 In one review of life review interventions, two RCTs found no significant differences in purpose in life between life review and control groups. Owing to reported heterogeneity, pooled estimates were not calculated.…”
Section: (In)mentioning
confidence: 99%
“…Life review/dignity therapy Adults and mixed samples Patient outcome: will to live 1 SR 100 Dignity therapy was associated with increased will to live in a single RCT described in the review.…”
Section: (Im In)mentioning
confidence: 99%
See 3 more Smart Citations